Optimization of Geometrical Parameters of Fire Wood Fluidized Bed Burner - Pivnenko Y.; Burda Y.; Redko I.; Cherednik A.,; Alferov S. (Problems of the Regional Energetics)
The aim of this work is to determine the dynamics of the firewood burning-out in the fluidized bed burners and to select the optimal constructive characteristics of the burner of the fluidized bed, which allows decreasing the unburnt fuel particles to be carried out of the burner volume. The aims and problems were solved using the experimental and numerical methods. Thus, to determine the dynamics of the burning-out, the experimental device was used with a fluidized bed, which is a 200x300 mm chamber 1000 mm high. The fuel mass of each combustion cycle was similar. It was 3.8 kg. The average time of burning-out during the combustion full cycle was in the range of 300-500 s, the maximum temperature of the layer was 800C. The studies per-formed showed that the major problem in the wood waste combustion is the insufficient time of the combustion process in the burner. This problem was proposed to be solved using the cone-shaped burner. The mathematical method was developed to determine the optimal main con-struction parameters (D is the top diameter; d is the bottom diameter and H is the cone height) of the burner accounting for the solid particle motion rate in the ascending flow. The devolatiliza-tion parameter of material was used as the optimization parameter. The most significant results are those cone-shaped geometrical parameters optimized in the research process. The signifi-cance of the results obtained is that the results of the above studies can be used in practice for designing the boilers with the fluidized bed burners.